2012
DOI: 10.3390/f3010083
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Cyclaneusma minus with Green Fluorescent Protein (GFP) to Enable Screening of Fungi for Biocontrol Activity

Abstract: Cyclaneusma needle-cast has a major impact on the New Zealand forest industry. The causal agent, Cyclaneusma minus, causes most severe damage to 11-20 year-old trees and currently there are no economically viable procedures for control of the disease in New Zealand. Here we present a method for genetic transformation of C. minus using protoplasts generated by incubation with Glucanex™ enzyme. C. minus was transformed with a gene encoding green fluorescent protein (GFP) and expression was stable after successiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Mandyam and Jumpponen () indicated that different host and fungal genotypes and broad functional groupings in the “ mutualism–parasitism continuum ” induce different host responses within host–fungus associations. For example, Cyclaneusma minus is able to act as an endophyte throughout its life cycle on some host genotypes (Sieber, Rys, & Holdenrider, ), but on other genotypes of the same host acts as a pathogen (Bulman, ; McDougal, Stewart, & Bradshaw, ). These host responses are modulated by various abiotic conditions or by the presence of other pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Mandyam and Jumpponen () indicated that different host and fungal genotypes and broad functional groupings in the “ mutualism–parasitism continuum ” induce different host responses within host–fungus associations. For example, Cyclaneusma minus is able to act as an endophyte throughout its life cycle on some host genotypes (Sieber, Rys, & Holdenrider, ), but on other genotypes of the same host acts as a pathogen (Bulman, ; McDougal, Stewart, & Bradshaw, ). These host responses are modulated by various abiotic conditions or by the presence of other pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…the introduction of multiple lytic enzyme-encoding genes into Trichoderma virens genome resulted in a strain that secreted a mixture of glucanases and showed greatly enhanced inhibition of the pathogens Pythium ultimum (Oomycota, Chromista), Rhizoctonia solani, and Rhizopus oryzae (Djonovic et al, 2007); (b). McDougal et al (2012) presented a method for the genetic transformation of Cyclaneusma minus, the causal agent of Cyclaneusma needle-cast, using protoplasts generated by incubation with Glucanex ™ enzyme. Cyclaneusma minus was transformed with a gene encoding green fluorescent protein (GFP), which was allowed to identify several Trichoderma strains with potential for biocontrol of the disease.…”
Section: Modern Biotechnological Approaches Used In Plant Fungal Pathmentioning
confidence: 99%
“…Investigations by Kowalski and Zych [41] revealed the qualitative and quantitative composition of mycobiota as a function of tissue type, age of asymptomatic shoots, and their location in P. nigra crowns. Some fungi, such as Cyclaneusma minus (Butin) DiCosmo, Peredo & Minter, a pathogen of needles, are able to infect and behave as an endophyte throughout their life cycle as found in P. radiata [47]. Furthermore, latent infections in P. nigra and P. sylvestris by D. sapinea without symptom development have also been observed [48].…”
Section: Pathway Of Spread Of D Septosporum In Europementioning
confidence: 99%
“…Although it has not been confirmed that pathogens such as D. septosporum can be transmitted under the seed coat, it is known that spores of pathogenic fungi can be transferred to pollen [45,46]. Some fungi, such as Cyclaneusma minus (Butin) DiCosmo, Peredo & Minter, a pathogen of needles, are able to infect and behave as endophytes throughout their life cycle [47]. Furthermore, latent infections in P. nigra and P. sylvestris by D. sapinea without symptom development have also been observed [48].…”
Section: Introductionmentioning
confidence: 99%